(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
Interaction of 2-(2-ethoxy-3-bromopropyl)-2-ethoxycarbonyl-4-butanolide with piperidines, morpholines and rodanines lead to the formation of new lacton-heterocycles.